Cannabinoid derivate-loaded PLGA nanocarriers for oral administration: formulation, characterization, and cytotoxicity studies - Prados J (Dove Medical Press, 2012)
Lucía Martín-Banderas,1 Josefa Álvarez-Fuentes,1 Matilde Durán-Lobato,1 José Prados,2 Consolación Melguizo,2 Mercedes Fernández-Arévalo,1 Mª Ángeles Holgado11Department of Pharmacy and Pharmaceutical Technology, Faculty of Pharmacy, University of Seville, Seville, Spain; 2Institute of Biopathology and Regenerative Medicine (IBIMER), School of Medicine, University of Granada, Granada, SpainAbstract: CB13 (1-Naphthalenyl[4-(pentyloxy)-1-naphthalenyl]methanone)-loaded poly(lactic-co-glycolic acid nanoparticles (NPs) were produced by nanoprecipitation and tested for their in vitro release behavior and in vitro cytotoxicity assays. The effects of several formulation parameters such as polymer type, surfactant concentration, and initial drug amount were studied. NPs had a particle size 90–300 nm in diameter. Results obtained show that the main influence on particle size was the type of polymer employed during the particle production: the greater the hydrophobicity, the smaller the particle size. In terms of encapsulation efficiency (%), high values were achieved (~68%–90%) for all formulations prepared due to the poor solubility of CB13 in the external aqueous phase. Moreover, an inverse relationship between release rate and NP size was found. On the other hand, low molecular weight and low lactide content resulted in a less hydrophobic polymer with increased rates of water absorption, hydrolysis, and erosion. NPs showed no cytotoxicity and may be considered to be appropriate for drug-delivery purposes.Keywords: neuropathic pain, CB13, nanoprecipitation